Issues and developments in international trade policy - Kelly, Margaret R.; International Monetary Fund (Washington, D.C. : International Monetary Fund, 1988)
The study reviews major issues and developments in the trade area and oulines the problems in the multilateral trading system that governments face as they seek to liberalize trade in the Uruguay Round of trade negotiations.
BIB
Keywords: International trade; Commercial policy